Pubertal development, physical activity, and sedentary behavior among South Korean adolescents - Lee Eun-Young (Acta Gymnica, 2017)
Background: Sex differences in physical activity (PA) and sedentary behavior (SB) are well-established. However, recent research suggested that variations in pubertal development may explain sex differences in PA and SB among adolescents. Objective: This study examined whether pubertal development mediates the relationship between sex and PA, and SB respectively. Methods: The 2012 Korea Youth Risk Behavior Web-based Survey included data from 74,186 students in grades 7 to 12 (mean age = 14.94 ± 1.8; 48.5% girls). Pubertal development was indicated by the year in which the student reported they had experienced menarche for girls and semenarche for boys. Testing for mediation involved a bootstrapping resampling approach with self-reported PA and SB as criterion variables and taking into account covariates (chronological age, body mass index, school type, household income, and parental education). Results: Boys engaged in PA more frequently (3.30 ± 2.1 vs. 2.29 ± 1.7 day/week) and spent less time in SB (2.75 ± 1.2 vs. 2.93 ± 1.2 hr/day) than girls. Direct effects were found between sex and PA (β = -0.58 ± .01; p < .05), and sex and SB (β = 0.17 ± 0.01; p < .05). Pubertal development did not significantly mediate the relationship between sex and PA (β = 0.00; bias-corrected 95% confidence interval [BC 95% CI] [-0.01, 0.01]). Though pubertal development significantly mediated the association between sex and SB, the effect was small (β = 0.01; BC 95% CI [0.00, 0.02]). Conclusions: Sex appears to be an important predictor of PA and SB. Nonetheless, it is most likely that a combination of individual (e.g., psychological, biological) and sociocultural factors contribute to adolescents' movement behavior.